A Study on the Antimicrobial Finishing of Rodalon on Silken Carpet (Journal of Fiber Bioengineering and Informatics, 2018)
In Iranian culture, carpet is the first choice for covering the floor; it is a very suitable substrate for growing pathogenic microbes. In this research, the main aim is to investigate the antibacterial effectiveness of rodalon solutions on silken fibers by spraying method used in silken carpet. Silken pile carpet laid in a public place (in VIP of The Homa hotel) for 30 days and some microbes found on them were investigated . The antimicrobial effect of different Rodalon solutions on the identified microbes was studied in vitro. The silken fibers were treated with solutions of Rodalon like before and the antimicrobial effectiveness was assessed by the zone of inhibition method at different times. Two pieces of carpet untreated and treated with Rodalon solution were sewed together and laid for two weeks in a public place and the amounts of bacterial growth on it was determined by colony count method and the results were compared. Finally some mechanical properties of treated silken fibers were measured after 30 days and was compared with untreated one. The results showed the presence of some pathogenic microbes on the laid carpet such as Escherichia coli and Staphylococcus aureus. The inhalation time for treated silken fibers was found to be improved. The amount of colony growth on treated carpet reduced considerably and moreover the mechanical test results showed no significant deterioration effect of studied properties in comparison to the untreated yarn.
Keywords: Rodalon; silken carpet; inhalation time; colony count; escherichia coli; staphylococcus aurous